Artificial intelligence and financial risk mitigation - Rehan, Raja; Sa'ad, Auwal Adam; Haron, Razali (Wiley, 2024)
The former approaches for financial risk mitigation are warranted to be revamped, as they are no longer effective. Nevertheless, the continuous advancement in fintech has developed artificial intelligence (AI), whose powered techniques are considered to be the most effective to identify and mitigate financial risk. Visibly, the financial sector as a whole is drastically altered by artificial intelligence, which gives rise to several procedures to mitigate probable financial risks. In this context, this chapter presents the AI-based financial risk detection process, which involves the main steps used to detect financial risk and then classify its types. Likewise, the established ongoing artificial intelligence-based financial risk mitigation process contains several steps that are used to lessen potential risk. Also, the strategies used by artificial intelligence to mitigate dissimilar sorts of financial risks are discussed in great detail in this chapter. Overall, this chapter discusses how quickly this modern technology provides benefits in terms of mitigating financial risks. As well, by adopting developed artificial intelligence-based financial risk identification and mitigation procedures, financial institutions can accurately evaluate massive information and identify financial risk factors, thus laying a more scientific, accurate, and comprehensive decision-making foundation for financial risk mitigation and management.